Folic acid enhances the apoptotic and genotoxic activity of carboplatin in HeLa cell line - Nikoloff, Noelia (2016)
In human tumor cells, experimental and clinical evidence indicates that some factors involved in signal transductionand cell growth can also modulate the response to chemotherapeutic treatment. The aim of the presentstudy was to investigate the role of folic acid (FA) as a modulator of carboplatin (CBDCA) activity.Genotoxicity and cytotoxicity induced by CBDCA alone and in combination with FA were assessed in culturedHeLa cells. We used comet assay, mitotic index analysis, MTT and NR assays, cytokinesis-block micronucleuscytome assay and annexin V-IP as different cytotoxicity and genotoxicity approaches for human cervical carcinomacell line studies.The results showed that addition of 900 nMFA together with 40.4mMCBDCA enhanced the activity of the platinumcompound,increasing its effect on cell death by nearly 20%, as evidenced by theMTT and NR assays. Moreover,not only higher levels of DNA and chromosomal damage were reached but also the number of necrotic andapoptotic cells were significantly increased when cell cultures were treated with the combined procedure.This situation opens the possibility to explore the use of FA in platinum-based chemotherapy protocols to reducethe platinum doses for patient treatment and decrease the chance of developing the known side effects withoutlosing biological activity.